The academic, business, and government collaboration in redefining global power: A contribution from smart power in the United States, China, and Russia in the context of artificial intelligence (2015-2025) - Salas Ocampo, Luis Diego (2025)
This article analyzes how collaboration between universities, businesses, and states has influenced the projection of global power in China, the United States, and Russia in artificial intelligence (AI) between 2015 and 2025. It examines how these actors have built smart power strategies that combine hard and soft dimensions to position themselves as leaders. The objectives were: (1) to identify the evolution of interest in AI in the three countries, (2) to establish regulatory and institutional milestones in academia–industry–government collaboration, and (3) to analyze the impact of university-generated knowledge on each nation’s soft power. The methodology included documentary analysis, critical discourse analysis, and comparison of regulatory frameworks. The results show that the U.S. promotes a flexible innovation model, China drives a centralized technological sovereignty strategy, and Russia consolidates capacities in security and defense. AI emerges as a key resource in geopolitical competition.